The influence of culture on the relationship between the entrepreneur's social identity and decision-making: Effectual and causal logic - M. EstradaCruz; Antonio Jose Verdú-Jover; José María Gómez-Gras (BRQ Business Research Quarterly, 2019)
Entrepreneurs' actions and attitudes towards business decisions are fundamental to new ventures. Building on Fauchart and Gruber (2011), which identifies three types of entrepreneurial social identity (Darwinian, communitarian, and missionary), this study analyzes how these identities influence use of effectual and causal logic, while also explaining the effect of the culture of the country in which the entrepreneurship initiative is developed. Based on a survey of 5076 founders who created their own venture, the results support the conclusion that the cultural dimensions defined as avoiding uncertainty, individualism, long term orientation, and distribution of power influence decisions made using effectuation.
Keywords: L26; M13; M10; 650; Causal logic; Cultural dimensions; Effectual logic; Social identity